High brightness red emitting polymer beads for immunoassays: Comparison between trifluoroacetylacetonates of Europium - Dinga, Daniel K.; Kasprzycka, Ewa; Assunção, Israel P.; Winterstein, Franziska; Alizade, Amina; Caliskanyürek, Volkan; Blödorn, Dirk; Winkle, Johannes; Kynast, Ulrich; Lezhnina, Marina (Frontiers in Chemistry, 2023)
Efficiently luminescing spherical polymer particles (beads) in the nanoscale regime of up to approximately 250 nm have become very valuable tools in bioanalytical assays. Eu3+- complexes imbedded in polymethacrylate and polystyrene in particular proved to be extraordinarily useful in sensitive immunochemical and multi-analyte assays, and histo- and cytochemistry. Their obvious advantages derive from both, the possibility to realize very high ratios of emitter complexes to target molecules, and the intrinsically long decay times of the Eu3+-complexes, which allows an almost complete discrimination against bothersome autofluorescence via time-gated measuring techniques; the narrow line emission in conjunction with large apparent Stokes shifts are additional benefits with regard to spectral separation of excitation and emission with optical filters. Last but not least, a reasonable strategy to couple the beads to the analytes is mandatory. We have thus screened a variety of complexes and ancillary ligands; the four most promising candidates evaluated and compared to each other were -diketonates (trifluoracetylacetonates, R-CO-CH-CO-CF3, R = - thienyl, -phenyl, -napthyl and -phenanthryl); highest solubilities in polystyrene were obtained with trioctylphosphine co-ligands. All beads had quantum efficiencies in excess of 80 % as dried powders and lifetimes well beyond 600 µs. Core-shell particles were devised for the conjugation to model proteins (Avidine, Neutravidine). Their applicability was tested in biotinylated titer plates using time gated measurements and a Lateral Flow Assay as practical examples.